Peran Mutasi dan Promosi dalam Pengembangan Karir dan Kinerja Pegawai - Ahsan, Krisna Pradipta (PRODUKTIF: Jurnal Kepegawaian dan Organisasi, 2024)
Transfers and promotions are important human resource management strategies in career development and improving employee performance. Dynamic changes in the business environment require organizations to adapt human resource needs effectively to achieve strategic goals. This research aims to analyze the role of transfers and promotions in employee career development and their impact on their performance. By understanding the transfer and promotion mechanisms, it is hoped that optimal career development strategies for employees and the organization can be identified. This research uses a qualitative approach with case studies in several companies. Data was collected through in-depth interviews with employees who had undergone transfers or promotions, as well as analysis of documents related to transfer and promotion policies within the organization. The results of the analysis show that transfers and promotions have a significant role in employee career development. Employees who experience transfers or promotions tend to have higher motivation to improve their performance. Apart from that, success in managing transfers and promotions also has a positive impact on employee loyalty to the organization.